Prognostic and Clinical Significance of Cyclooxygenase-2 Overexpression in Endometrial Cancer: A Meta-Analysis - Li, Mingli; Li, Mingxuan; Wei, Yangang; Xu, Hua (Frontiers in Oncology, 2020)
Objective: Cyclooxygenase-2 (COX-2) is a critical enzyme associated with inflammation and tumorigenesis. Although several studies have compared the expression of COX-2 in endometrial cancer tissues and normal tissues, the results have been inconsistent thus far. This study aims to conduct a meta-analysis to elucidate the role of COX-2 in the determination of the risk, prognosis, and clinical features of endometrial cancer. Methods: We retrieved the suitable studies on the association between COX-2 expression and endometrial cancer from PubMed, EMBASE, and Web of Science databases that were published between 1999 and September 31st, 2019. The hazard ratios (HRs) and 95% confidence intervals (CIs) were retrieved to assess the relationship between COX-2 expression and the prognosis of endometrial cancer. The odd ratios (OR) and 95% CIs were calculated to evaluate the correlation between COX-2 expression and the risk and clinical features of endometrial cancer. Results: To investigate the association between COX-2 expression and the susceptibility, clinical features, and prognosis of endometrial cancer, we performed a meta-analysis on data from selected studies that collectively involved 273 normal individuals and 1,376 patients with endometrial cancer. Overall, the pooled analysis indicated that COX-2 expression was significantly associated with susceptibility (Caucasians, OR = 3.94, 95% CI = 2.17 – 7.17, P < 0.05; Asians, OR = 20.51, 95% CI = 8.54 – 49.26, P < 0.05), cancer stage (OR = 3.01, 95% CI = 1.95 – 4.67, P < 0.05), myometrial invasion (OR = 1.59, 95% CI = 1.17 – 2.15, P < 0.05), lymph node metastasis (OR = 1.63, 95% CI = 1.18 – 2.26, P < 0.05), and prognosis (OR = 2.91, 95% CI = 1.17 – 4.66, P < 0.05) in endometrial cancer. Conclusions: Our findings suggested that COX-2 overexpression is significantly associated with poor prognosis and advanced clinical features in endometrial cancer. Therefore, COX-2 may function as an effective prognostic biomarker and a potential therapeutic target for endometrial cancer.